THE INTERSECTION OF HEALTH LAWS AND HUMAN RIGHTS IN THE CONTEXT OF HIV-POSITIVE COUPLES - Sesulih, Retno; Noor, M. Tauchid; Adriano (JILPR Journal Indonesia Law and Policy Review, 2024)
Legal protection for partners of persons living with HIV (PLHIV) is the subject of this study. This study employs a form of normative juridical research that combines conceptual and statutory methodologies. A literature review was conducted to collect and analyze all legal materials utilized in this research. Deductive legal materials were employed for analysis. These are the outcomes of this research: 1) The relationship between health law and human rights in couples comprising people living with HIV (PLHIV) is reciprocal. Human rights violations frequently lead to health disruptions, and conversely, infringements upon the right to health constitute human rights violations. In the same way that health services must be universal and not discriminatory in accordance with the right to health, it is impermissible to deny access to health services to patients, including those who are partners of people living with HIV (PLHIV). 2) Legal protection for partners of persons living with HIV (PLHIV) is governed by the ICESCR, the ICCPR (Human Rights Law), and health-related legislation, including Health Law No. 17 of 2023. Human rights legislation is a reflection of societal values, specifically tolerance and nondiscrimination. Nonetheless, this legislation has yet to manifest empathy due to the absence of a concern-filled attitude towards the partners of individuals living with HIV.